Vida Saludable: Diabetes - Linda B. Bobroff; Karla P. Shelnutt; Paulina Wittkowsky (EDIS)
Revised! FCS8574-Span, a 3–page fact sheet by Linda Bobroff, Karla Shelnutt, and Paulina Wittkowsky, contains basic information on what diabetes is, who is at risk, and how the disease can be controlled. Revised to add more resources and to provide a new chart that can help determine whether you are at a healthy weight.